PWE-122 The results of endoscopic and surgical treatment for achalasia in england between 2005 and 2016. (17th June 2017) - Harvey, P; Coupland, B; Mytton, J; Patel, P; Trudgill, N
Abstract : Introduction: Achalasia is an uncommon condition characterised by failed relaxation of the lower oesophageal sphincter. Achalasia can be treated by botulinum toxin injection, pneumatic dilatation, Heller's myotomy or per-oral endoscopic myotomy. The aim of this study is to examine long term outcomes of the major treatment modalities. Method: The Hospital Episode Statistics (HES) database includes diagnostic and procedural data for all hospital attendances in England. All subjects with an ICD10 code for achalasia and initial treatment between January 2006- September 2016 were grouped by coded initial treatment; injection, endoscopic dilatation or surgery. Procedural success was defined by time to further treatment, in the case of dilatations up to 3 procedures over 10 years were considered to not be a failure. Adverse events were recorded per procedure and predictors sought by logistic regression. Results: 7373 subjects were included of whom 3828 (51.9%) were male, mean age at diagnosis 59.6 years (SD 19.75). 435 initially received (5.90%) endoscopic injection, 4748 (64.4%) dilatation and 2190 (29.7%) underwent surgery. Perforation rate following dilatation was 1.62%. Charlson score was 1–4 in 8.74%, 10.00%, 10.87% and >4 in 13.33%, 12.64%, 3.01% of the injection, dilatation and surgical groups respectively. Mortality at 30 days was; 2.99%, 1.87%, 0%, for the Injection, dilatation and surgical groups respectively. Factors predicting mortality after dilation included; age quintiles 66–77 (OR 3.94, 95% CI 1.83–8.46, p<0.001), >77 (7.93, 3.74–16.81, p<0.001), Charlson co-morbidity score >4 (2.99, 2.21–4.04 p<0.001), and previous surgical treatment (2.03, 1.09–3.78, p=0.025). Only Charlson score >4 (2.55 (1.11–5.85 p<0.028) predicted mortality in those receiving endoscopic injection. Durability for each group of single initial treatment at 9 years follow-up was 19.23%, 43.97%, 85.78% for injection, dilatation and surgical treatment respectively. The durability of up to 3 dilatations compared to single surgical treatment is reported in the table below. Conclusion: The durability of surgical and pnuematic dilatation therapy for achalasia appears to be similar over up to 9 years. There was no mortality associated with surgery but 1.87% of subjects died within 30 days of dilatation. Older age and increased co-morbidity predicted mortality in subjects. Disclosure of Interest: None Declared